The Effect of Soil Survey Adequacy on Engineering Design Details (DED) on Potential Cost and Construction Time Savings - Ilham Akbar Mulya Wibawa; Bambang Endro Yuwono; Darmawan Pontan; Tulus Widiarso (Eduvest - Journal of Universal Studies, 2025)
The construction of the Kadusirung Dua Underpass Project in Banten aimed to improve access routes but encountered landslides during execution, necessitating design changes and additional soil investigations. This study examined the impact of inadequate soil surveys on engineering design, focusing on cost and time efficiency. The research objectives were to analyze the effects of design changes during construction, compare initial and revised designs, and evaluate savings potential if proper soil investigations were conducted initially. Using secondary data from the project, the study employed Microsoft Project for time-cost analysis and applied the Cost of Change vs. Opportunity to Influence theory. Findings revealed that design changes during construction increased costs by Rp 43.6 billion and extended the timeline by 566 days. Conversely, comprehensive soil surveys at the planning stage could have saved 25% of the time (237 days) and 18% of costs (Rp 38.9 billion). The implications highlight the critical need for thorough geotechnical investigations early in projects to mitigate delays and cost overruns. The study underscores the importance of adhering to soil testing standards (SNI 8460:2017) and optimizing design decisions during planning to enhance project efficiency.